Synthesis and characterization of MgFe2O4 for photo-catalytic degradation of pre-treated pome - Nyap Xiang, Wong (2015)
Edible oil production from Malaysia currently accounts for 12% and 27% of the world's total production and exports of oils and fats. Consequently, the palm oil industry also discharges substantial waste during the oil processing in the form of oil palm trunks, oil palm fronds (OPF), empty fruit bunches, palm kernel shells and palm oil mill effluent (POME). The current work reports the use of ferrite based photocatalyst for the photodegradation of POME that was collected from Felda Lepar Hilir 3. X-ray diffraction pattern confirmed the presence of MgFe2O4 with crystalline size ranged from 25.4 to 50.5 nm estimated using Scherrer‟s formula. Significantly, N2 physisorption isotherm revealed a BET specific surface area of 4.87 m²/g and pore diameter of 205.23 nm. Transmission Electron Micrograph (TEM) showed d-spacing for MgFe2O4 atomic lattice which was 0.298 nm. FESEM-EDX analysis indicated that MgFe2O4 nano-particles were comprised of Mg, Fe and O elements with compositions of 22.5, 43.04 and 34.7 wt%, respectively. For the photoreaction study, before the POME photodecomposition investigation, the photoactivity of catalysts was tested with methylene blue (MB). MB that initially showed a concentration of 20 ppm exhibited significant photodegradation (%) after 90 min of light irradiation, attaining approximately 20% conversion. For POME, the degradation of POME was circa 9% after 4 h employing catalyst loading of 1.0 g/L, which was superior to 5.0, 2.0 and 0.5 g/L. As a conclusion, phototreatment for POME showed positive results, and may be feasible for POME treatment eventually